(untitled) (JURNAL ULET (Utility, Earning and Tax), 2024)
This research aims to determine Kios Anggun’s ability to generate profits from sales, utilize its assets to generate profits, demand for assets and capital to generate profits. This research is descriptive research with data collection techniques using interview and documentation techniques. The data analysis instruments used in this research are profitability analysis, net profit margin, return on assets, return on equity. The results of the analysis show that the profits from total sales that occur in the category are not good. As shown by the net profit margin ratio in 2019-2021 of 7.23%, 3.68% and 4.45% respectively, the profit from the total assets owned is in the quite good category. As shown by the return on asset ratio in 2019-2021 of 8.83%, 5.47% and 6.71% respectively, the profit from the capital it owns is in the good category. This is shown by the return on equity ratio in 2019-2021 of 9.98%, 5.96% and 6.98%, respectively.